Effectiveness of barrier precautions for prevention of patient-to-patient transfer of a viral DNA surrogate marker. (17th September 2021) - Alhmidi, Heba; Cadnum, Jennifer L.; Ng-Wong, Yilen K.; Jencson, Annette L.; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: Background: Gloves and gowns are used during patient care to reduce contamination of personnel and prevent pathogen transmission. Objective: To determine whether the use of gowns adds a substantial benefit over gloves alone in preventing patient-to-patient transfer of a viral DNA surrogate marker. Methods: In total, 30 source patients had 1 cauliflower mosaic virus surrogate marker applied to their skin and clothing and a second to their bed rail and bedside table. Personnel caring for the source patients were randomized to wear gloves, gloves plus cover gowns, or no barrier. Interactions with up to 7 subsequent patients were observed, and the percentages of transfer of the DNA markers were compared among the 3 groups. Results: In comparison to the no-barrier group (57.8% transfer of 1 or both markers), there were significant reductions in transfer of the DNA markers in the gloves group (31.1% transfer; odds ratio [OR], 0.16; 95% confidence interval [CI], 0.02-0.73) and the gloves-plus-gown group (25.9% transfer; OR, 0.11; 95% CI, 0.01–0.51). The addition of a cover gown to gloves during the interaction with the source patient did not significantly reduce the transfer of the DNA marker ( P = .53). During subsequent patient interactions, transfer of the DNA markers was significantly reduced if gloves plus gowns were worn and if hand hygiene was performed ( P < .05). Conclusions: Wearing gloves or gloves plus gowns reduced the frequency of patient-to-patient transfer of a viral DNA surrogate marker. The use of gloves plus gowns during interactions with the source patient did not reduce transfer in comparison to gloves alone.